Exploring Talim's forest a community-based management approach to forest conservation and livelihoods on Talim Island, Rizal - Eden, Fara Marie Ina B.
Forests play a significant role in the lives of millions of people around the world. They contribute a wide range of ecosystem services and benefits to many individuals and groups of people, such as the social and economic well-being of the communities. Furthermore, the forest ecosystem services provide a wide variety of products and opportunities to these growing populations. Forest-dependent communities, or people who live within or adjacent to the forests, usually depend on forests and forestlands for their income and subsistence, maintaining their basic necessities and livelihoods. In particular, the mountainous forest island of Talim located at the center of Laguna Lake, is characterized by natural features and vegetation, including non-timber forest resources such as bamboo, which is a significant source of income and livelihood to the local communities residing within the area. However, existing literature has reported a decline in forest resources and some reports have observed land degradation as a result of population growth and increased resource exploitation. For this reason, the study aims to identify the current livelihood practices and resource management related to the forests, and investigate the possible exploitive activities by the people and communities in the island. In order to achieve its goal, the study will explore and analyze the community-based management approach in protecting the forests and their natural resources, while ensuring the community welfare in the Talim Island. Moreover, this study shall demonstrate the importance of collaborative and participatory approach in the implementation of sustainable forest management practices and enhancement of the local livelihoods of the communities in Talim Island, Rizal.